Synthesis and biological evaluation of triphenyl-imidazoles as a new class of antimicrobial agents - Anupam, Anupam; Al-Bratty, Mohammed; Alhazmi, Hassan Ahmad; Ahmad, Shamim; Maity, Supriya; Alam, Md Shamsher; Ahsan, Waquar (European Journal of Chemistry, 2018)
Newer triphenyl-imidazole derivatives (4a-h) were synthesized in good yields by the reaction of benzil and substituted benzaldehydes in equimolar quantities and refluxing the product with acetyl chloride thereafter. Structures were confirmed by using FT-IR, 1H NMR and 13C NMR spectroscopic methods. All the synthesized compounds were tested for their antimicrobial activity using agar diffusion technique against Gram positive (Staphhylococcus aureus and Bacillus subtilis), Gram negative (Escherichia coli and Pseudomonas aureginosa) as well as Fungal strain (Candida albicans). Interestingly compounds 4a, 4b, 4f and 4h showed significant antibacterial activity, whereas compound 4b was found to have remarkable activity against the fungal strain. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of most active compounds were determined by broth dilution method and compound 4b emerged to have potent activities against most of the strains having MIC in the range of 25-200 µg/mL. To check the possible toxicities of the most active compounds, they were orally administered in rats and the concentration of liver enzymes serum glutamic-oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT) and alkaline phosphatase (ALKP) were determined. Compound 4h showed significant increase in the enzymes level depicting the hepatotoxicity. The structure-activity relationship studies showed the importance of electron withdrawing groups at the distant phenyl ring at ortho and para positions as the compounds having chloro or nitro at these positions tend to be more active than the compounds with electron releasing groups such as methoxy. These compounds may act as lead compounds for further studies and appropriate modification in their structure may lead to agents having high efficacy with lesser toxicity.